1979
DOI: 10.1002/pssb.2220940235
|View full text |Cite
|
Sign up to set email alerts
|

Optical identification of substitutional acceptors in refined ZnTe

Abstract: A systematic study of acceptors incorporated by diffusion is carried out on refined melt-grown ZnTe. The properties of five substitutional acceptors are investigated by low-temperature photoluminescence. Since the binding energy of excitons on neutral acceptors is almost unaffected by the central cell potential, the neutral acceptors are identified by the two-hole transitions which give accurate values of acceptor ionization energies. The two dominant acceptors "b" at 61 meV and "a" a t 149 meV are identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
1

Year Published

1979
1979
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(14 citation statements)
references
References 25 publications
4
9
0
1
Order By: Relevance
“…This phenomenon has been already observed in other materials [4,7,20,211, for THT, and is well explained by interaction between a LO phonon and the bound particle. If the LO phonon energy is somewhat greater than the bound particle binding energy, the following virtual interaction can occur:…”
Section: Diffusionsupporting
confidence: 78%
“…This phenomenon has been already observed in other materials [4,7,20,211, for THT, and is well explained by interaction between a LO phonon and the bound particle. If the LO phonon energy is somewhat greater than the bound particle binding energy, the following virtual interaction can occur:…”
Section: Diffusionsupporting
confidence: 78%
“…However, we find that the T d symmetric ground state with a delocalized effective‐mass like hole wave‐function (PHS) lies 0.3 eV lower in energy than the symmetry‐broken configuration. Thus, the generalized Koopmans formalism correctly predicts the well established effective‐mass behavior of Li Zn in ZnTe, and the calculated Li acceptor ionization energy of 0.08 eV reflects the shallow effective‐mass acceptor level (experiment: 0.06 eV 89). Shallow ground state without barrier (Fig.…”
Section: The Balance Between Localization and Delocalizationmentioning
confidence: 60%
“…We have shown that the p-type conductivity of ZnTe originates mainly from CuZn [2] and Lizn [3], and for a smaller part from Agzn [a] rather than from intrinsic defects. The infrared absorption spectra of As, P, and Li acceptors in ZnTe have been published [5].…”
Section: Introductionmentioning
confidence: 99%